Brain α7 nicotinic acetylcholine receptors in MPTP-lesioned monkeys and parkinsonian patients - Morissette, Marc; Morin, Nicolas; Grégoire, Laurent; Rajput, Alex; Rajput, Ali H.; Di Paolo, Thérèse (Biochemical pharmacology, 2016)
[Display omitted] L-DOPA-induced dyskinesias (LID) appear in the majority of Parkinson’s disease (PD) patients. Nicotinic acetylcholine (nACh) receptor-mediated signaling has been implicated in PD and LID and modulation of brain α7 nACh receptors might be a potential therapeutic target for PD. This study used [125I]α-Bungarotoxin autoradiography to investigate α7 nACh receptors in LID in post-mortem brains from PD patients (n=14) and control subjects (n=11), and from 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned monkeys treated with saline (n=5), L-DOPA (n=4) or L-DOPA+2-methyl-6-(phenylethynyl)pyridine (MPEP) (n=5), and control monkeys (n=4). MPEP is the prototypal metabotropic glutamate 5 (mGlu5) receptor antagonist; it reduced the development of LID in these monkeys. [125I]α-Bungarotoxin specific binding to striatal and pallidal α7 nACh receptors were only increased in L-DOPA-treated dyskinetic MPTP monkeys as compared to controls, saline and L-DOPA+MPEP MPTP monkeys; dyskinesia scores correlated positively with this binding. The total group of Parkinsonian patients had higher [125I]α-Bungarotoxin specific binding compared to controls in the caudate nucleus but not in the putamen. PD patients without motor complications had higher [125I]α-Bungarotoxin specific binding compared to controls only in the caudate nucleus. PD patients with LID only had higher [125I]α-Bungarotoxin specific binding compared to controls in the caudate nucleus and compared to those without motor complications and controls in the putamen. PD patients with wearing-off only, had [125I]α-Bungarotoxin specific binding at control values in the caudate nucleus and lower in the putamen. Reduced motor complications were associated with normal striatal α7 nACh receptors, suggesting the potential of this receptor to manage motor complications in PD.